2016
DOI: 10.1016/j.jdiacomp.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes medications: Impact on inflammation and wound healing

Abstract: Chronic wounds are a common complication in patients with diabetes that often lead to amputation. These non-healing wounds are described as being stuck in a persistent inflammatory state characterized by accumulation of pro-inflammatory macrophages, cytokines and proteases. Some medications approved for management of type 2 diabetes have demonstrated anti-inflammatory properties independent of their marketed insulinotropic effects and thus have underappreciated potential to promote wound healing. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 72 publications
(85 reference statements)
2
108
0
3
Order By: Relevance
“…We found profound changes in serum hormonal profiles of pre-pubertal non-obese allergic children compared to non-allergic controls, as well as chronic rhinosinusitis patients compared to healthy controls, including decreased levels in serum insulin and increased output of thyroid and growth hormones 96 . Hormones play a critical role in maintenance of epithelial barrier homeostasis and integrity via their integration with epithelial morphogenetic programs 88, 97 , evidenced by deficiencies in wound healing and epithelial dysfunction in patients with thyroid disease and diabetes 98, 99 . Insulin and IGF-1 are essential drivers of epithelial differentiation and regulators of energy metabolism.…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%
“…We found profound changes in serum hormonal profiles of pre-pubertal non-obese allergic children compared to non-allergic controls, as well as chronic rhinosinusitis patients compared to healthy controls, including decreased levels in serum insulin and increased output of thyroid and growth hormones 96 . Hormones play a critical role in maintenance of epithelial barrier homeostasis and integrity via their integration with epithelial morphogenetic programs 88, 97 , evidenced by deficiencies in wound healing and epithelial dysfunction in patients with thyroid disease and diabetes 98, 99 . Insulin and IGF-1 are essential drivers of epithelial differentiation and regulators of energy metabolism.…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%
“…Drugs studied showed potency in stimulating angiogenesis and formation of granulation tissue necessary in wound healing. 21 Oral mucosa in diabetic patients has different structure to people without DM due to prolong hyperglycemic condition. Insulin deficiency was assumed to have a direct effect in changes of vascularization and blood flow to the connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The initial stage of repair and the proliferation of apoptosis after deep burns has the following adverse effects: Growth factor expression is weakened, granulation of the wounded tissues is not normal and consequently the survival rate of free flaps is not high due to the lack of a nurturing environment. Previous experiments conducted on animals have revealed that local application of low-dose insulin can promote wound healing in a diabetic rat model with scalds (8). High glucose conditions may lead to suppression of vascular endothelial cell proliferation, weakened cell contacts and increased apoptosis of the cells.…”
Section: Discussionmentioning
confidence: 99%